Innovative fertilization strategies for in-situ pollution control and carbon negativity enhancement in agriculture - Ya-Zhen Huang; You-Yi Lee; Chihhao Fan (Agricultural Water Management)
Non-point source pollution resulting from agricultural fertilization may enter neighboring water bodies, negatively impacting the environmental water quality. Therefore, this study aims to evaluate the efficiency of innovative fertilization strategies for agricultural non-point source pollution control and explore their benefit for carbon negativity. The results show that organic fertilizers are more likely to be washed out by rainfall or irrigation due to their higher soluble component content. The treatments using bamboo biochar, microbial agents, or both significantly reduced the nitrogen concentrations in infiltration and surface runoff. The washed-away phosphate demonstrated a different trend because adding microbial agents, including phosphorus-solubilizing bacteria, converted fixed inorganic phosphorus in the soil into water-soluble phosphorus. In addition, the scouring and leaching in rainfall events mainly cause the farmland's nutrient loss after fertilizer application. The nutrient uptake by crops was increased by 15–30 %, and nutrient mass in infiltration and runoff waters was reduced by 5–10 %. By combining fertilizer reduction and innovative fertilization strategies, the crop yield remained similar to that with a full amount of fertilizer application. Over-dose application in fertilizer may not necessarily promote crop growth but may cause crop damage and fertilizer loss. The carbon negativity benefit of using innovative fertilization strategies was explored, and adding both microbial agents and bamboo biochar in half organic fertilization demonstrated the highest reduction (80.75 %) in carbon emission through synergistic interactions in the soil matrix. The innovative fertilization strategies employed in this study can (1) effectively reduce non-point source pollution from agricultural activities without impairing crops' overall growth and yield and (2) induce the synergistic effects in reducing nutrient loss, enhancing soil carbon sequestration, and mitigating greenhouse gas emissions.